Gabapentin Decreases Morphine Consumption and Improves Functional Recovery following Total Knee Arthroplasty - Hance Clarke; Sara Pereira; Deborah Kennedy; Ian Gilron; Joel Katz; Jeffrey Gollish; Joseph Kay (Pain Research and Management)
BACKGROUND: Moderate to severe pain after total knee arthroplasty often interferes with postoperative rehabilitation and delays discharge from hospital. The present study examined the effects of a four-day postoperative gabapentin (GBP) regimen versus placebo on opioid consumption, pain scores and knee flexion, as well as adverse effects, after total knee arthroplasty.